Strategi Politik Tokoh Utama dalam Novel Negeri di Ujung Tanduk Karya Tere Liye - Fanesha, Icha Fina; Sugiarti, Sugiarti (KLITIKA Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The main character's political strategy is to try to restore politics to a truly democratic system in achieving a goal, so the main character designs a political strategy. This research aims explain (1) the forms of the political strategy of the main character in Tere Liye's novel Negeri di Ujung Tanduk and (2) the types of the political strategy of the main character in Tere Liye's novel Negeri di Ujung Tanduk. The method applied to this analysis is the qualitative descriptive method. The results of the analysis determine that the main character must use various forms and types of a political strategy to maintain power. The main character uses a form of political strategy in the form of an open struggle carried out in public and a secret struggle carried out a secret, and under camouflage. As well as using the types of political strategies in the form of a defect strategy, a per nast strategy, and a surprise strategy. Analysis has shown that the main figure has been able to maintain power using the created form and type of political strategy, so that cannot undermine or usurp power from the clients.